Productivity and Economics of Intercropping of Finger Millet (Eleusine coracana) and Amaranth (Amaranthus spp.) in Rainfed Hills of Uttarakhand - Kumar, Ajay; Paliwal, Arunima; Singh, S. B.; T. S., Sukanya; Kishore, Amit (International Journal of Bio-resource and Stress Management, 2022)
A field experiment on finger millet (Eleusine coracana (L.) Gaertn.) and amaranth ( Amaranth spp.) intercropping was carried out for two consecutive years during kharif season of 2016 and 2017 at College of Forestry, Ranichauri, Tehri Garhwal, Uttarakhand, India to identify the most promising intercropping systems for improving productivity of cropping system followed in rainfed hills of Uttarakhand. Seven treatments consist of T1: Sole finger millet, T2: Sole Amaranth, T3: Finger millet+Amaranth (4:1) T4: Finger millet+Amaranth (90:10), T5: Finger millet+Amaranth (85:15), T6: Finger millet+Amaranth (80:20), T7: Farmer’s practice of Finger millet+Amaranth (60:40) was laid out in a randomized block design with three replications. Finger millet + Amaranth (90:10) i.e., T4, produced 58.8% higher finger millet grain equivalent yield (FMEY) over farmer’s practice (T7) of finger millet and amaranth (60:40) and 27.7% higher than the sole amaranth ( T2). The significantly higher finger millet straw equivalent yield was recorded in sole FM (T1) than farmers practice (T7) and was statistically on par with finger millet+amaranth (4:1) (T3) and finger millet+amaranth (90:10) (T4) However, highest land equivalent ratio (1.12), net returns (Rs. 31366 ha-1) and benefit cost: ratios (2.30) were also recorded with (T4) finger millet+ amaranth (90:10 ratio). The lowest benefit cost ratio (1.12) was registered in (T7) farmer’s practice. Therefore line sowing of finger millet+amaranth (90:10 ratios) would be more beneficial than the mixed cropping in rainfed hills of Uttarakhand.